Voriconazole-Induced Periostitis Mimicking Chronic Graft-versus-Host Disease after Allogeneic Stem Cell Transplantation. (14th June 2016) - Sweiss, Karen; Oh, Annie; Rondelli, Damiano; Patel, Pritesh
Abstract : Voriconazole is an established first-line agent for treatment of invasive fungal infections in patients undergoing allogeneic stem cell transplantation (ASCT). It is associated with the uncommon complication of periostitis. We report this complication in a 58-year-old female undergoing HSCT. She was treated with corticosteroids with minimal improvement. The symptoms related to periostitis can mimic chronic graft-versus-host disease in patients undergoing HSCT and clinicians should differentiate this from other diagnoses and promptly discontinue therapy.